Ecological aspects of the sandfly fauna (Diptera, Psychodidae) in an American cutaneous leishmaniasis endemic area under the influence of hydroelectric plants in Paranapanema river, State of Paraná, Brazil - Mariza Fordellone Rosa Cruz; Eunice Aparecida Bianchi Galati; Carolina Fordellone Rosa Cruz (Revista da Sociedade Brasileira de Medicina Tropical, 2012)
INTRODUCTION: An epidemiological study was undertaken to identify determinant factors in the occurrence of American cutaneous leishmaniasis in areas under the influence of hydroelectric plants in Paranapanema river, State of Paraná, Brazil. The ecological aspects of the phlebotomine fauna were investigated. METHODS: Sandflies were sampled with automatic light traps from February 2004 to June 2006 at 25 sites in the urban and rural areas of Itambaracá, and in Porto Almeida and São Joaquim do Pontal. RESULTS: A total of 3,187 sandflies of 15 species were captured. Nyssomyia neivai predominated (34.4%), followed by Pintomyia pessoai (32.6%), Migonemyia migonei (11.6%), Nyssomyia whitmani (8.8%), and Pintomyia fischeri (2.7%), all implicated in the transmission of Leishmania. Males predominated for Ny. neivai, and females for the other vector species, with significant statistical differences (p < 0.001). Nyssomyia neivai, Pi. pessoai, Ny. whitmani, Brumptomyia brumpti, Mg. migonei, and Pi. fischeri presented the highest values for the Standardized Species Abundance Index (SSAI). The highest frequencies and diversities were found in the preserved forest in Porto Almeida, followed by forests with degradation in São Joaquim do Pontal and Vila Rural. CONCLUSIONS: Sandflies were captured in all localities, with the five vectors predominating. Ny. neivai had its highest frequencies in nearby peridomestic environments and Pi. pessoai in areas of preserved forests. The highest SSAI values of Ny. neivai and Pi. pessoai reflect their wider dispersion and higher frequencies compared with other species, which seems to indicate that these two species may be transmitting leishmaniasis in the area.